Analisis Faktor yang Memengaruhi Perilaku Ibu Hamil dalam Pemeriksaan HbsAG - Pemula, Giok; Zuraida, Reni; Susianti, S (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
HBsAg examination is important to detect Hepatitis B in pregnant women, so it needs to be done during the first visit with the help of health. The results of the pre-survey at the Way Kandis Health Center in 2020, it was found that only 55.2% of pregnant women performed HbsAg examinations. The Purpose of the study was to determine the factors that influence the behaviour of pregnant women in the HBsAg examination at Way Kandis Health Center, Bandar Lampung City, in 2021. The design of this study was analytic with a cross-sectional approach. The number of samples in this study was 112 pregnant women, with a sampling technique of accidental sampling. Bivariate analysis using Chi-square. The results of the univariate study found that most pregnant women, 50.9% did not perform HBsAg examination, most of the pregnant women have less knowledge of 53.6%, the attitudes of pregnant women were negative 57.1%, the perception of pregnant women was negative 50.9%. Most of the distance travelled to close health services is 57.1%, negative husband support is 50.9%. The results of the bivariate test showed that there was a significant relationship between knowledge of attitudes, perceptions, distance travelled, husband's support with the behaviour of pregnant women with HBsAg examination at Way Kandis Health Center, Bandar Lampung City in 2021.  Abstrak: Pemeriksaan HbsAg merupakan hal penting untuk mendeteksi Hepatitis B pada ibu hamil, sehingga perlu dilakukan pada saat kunjungan pertama di tenaga kesehatan. Hasil prasurvei di Puskesmas Rawat Inap Way Kandis pada tahun 2020, didapatkan hanya 55,2% ibu hamil yang melakukan pemeriksaan HbsAg. Tujuan penelitian ini untuk mengetahui faktor-faktor yang memengaruhi perilaku ibu hamil dalam pemeriksaan HbsAg di Puskesmas Rawat Inap Way Kandis Kota Bandar Lampung Tahun 2021. Desain penelitian ini adalah analitik dengan pendekatan cross sectional. Jumlah sampel pada penelitian ini 112 ibu hamil, dengan tekhnik pengambilan sampel accydental sampling. Analisa bivariat menggunakan Chi-square. Hasil penelitian univariat didapatkan bahwa sebagian besar ibu hamil 50,9% tidak melakukan pemeriksaan HbsAg, sebagian besar pengetahuan ibu hamil kurang 53,6%, sikap ibu hamil negatif 57,1%, persepsi ibu hamil negatif 50,9 %. Sebagaian besar jarak tempuh kepelayanan kesehatan dekat yaitu 57,1%, dukungan suami negatif 50,9%. Hasil uji bivariat didapatkan ada hubungan yang bermakna antara pengetahuan sikap, persepsi, jarak tempuh, dukungan suami dengan perilaku pemeriksaan HbsAg ibu hamil di Puskesmas Rawat Inap Way Kandis Kota Bandar Lampung Tahun 2021.